Analysis of Load Balancing Effectiveness Using Per Connection Classifier (PCC) on Mikrotik Router (Karapan Network Journal : Journal Computer Technology and Mobile Ad Hoc Network, 2025)
The growing demand for digital services such as e-learning, video conferencing, and access to academic information systems requires a stable and high-capacity internet network. Reliance on a single ISP often leads to bottlenecks, increased delay, jitter, and packet loss during peak hours. One effective solution is implementing load balancing in multi-ISP configurations. This study analyzes the effectiveness of the Per Connection Classifier (PCC) load balancing method on Mikrotik RouterOS by assessing Quality of Service (QoS) parameters, namely throughput, delay, jitter, and packet loss.The study used an experimental approach with two scenarios: without load balancing as the baseline, and with PCC implementation. The results showed that PCC significantly increased throughput, decreased delay, stabilized jitter, and reduced packet loss compared to the baseline. The PCC hashing mechanism proved consistent in distributing connections to two ISPs with different capacities without causing session breaks. Evaluations based on TIPHON and ITU-T standards indicate that network performance after PCC implementation is in the good to excellent category. This study confirms that PCC is an effective and efficient load balancing method for optimizing medium-scale institutional networks that require high service availability and real-time traffic stability.
Keywords: Load Balancing, Per Connection Classifier (PCC), Mikrotik RouterOS, Quality of Service, Multi-ISP Network, Network Performance Optimization.